ХАЛЫҚАРАЛЫҚ ҚҰҚЫҚ ПЕН ҚАЗАҚСТАН ЗАҢНАМАСЫ БОЙЫНША ГЕНОЦИД ҚЫЛМЫСЫ ҮШІН ЖАУАПКЕРШІЛІК ТҮРЛЕРІ (Journal of actual problems of jurisprudence, 2019)
Thus, the offenderthe form of recovery of damage caused by the state is determined by the legislation of the state responsible for genocide.(material) responsibility should be attributed. These include: restitution, compensation(compensation), interest.